The application of Communicative Language Teaching in English education at Chinese universities: the serial mediation role of classroom atmosphere and second language acquisition self-efficacy - Chen, Yiran; Yin, Hao; Faya Ornia, Maria Goretti (Frontiers in Education, 2026)
With the in-depth development of English language teaching reform, the effectiveness of Communicative Language Teaching Method (CLT) and its mechanism of action in Chinese colleges and universities need to be studied in depth. Based on social cognitive theory and social constructivism, this study constructed a theoretical model of “CLT classroom participation - classroom atmosphere - self-efficacy in second language acquisition - commitment to second language learning,” and through a systematic survey of 656 college students from 7 colleges and universities across the country, the study reveals the innovative path of CLT in the Chinese educational context. The study found that: (1) CLT classroom participation positively affects students’ engagement in second language learning; (2) classroom atmosphere mediates the influence of CLT classroom participation on students’ engagement in second language learning; (3) self-efficacy for second language acquisition mediates the influence of CLT classroom participation on students’ engagement in second language learning; and (4) classroom atmosphere and self-efficacy form a chained mediation path. This finding breaks through overcomes the limitations of traditional CLT research that examines instructional variables in isolation. It is the first time that social cognitive theory and social constructivism have been systematically integrated, and a model of CLT mechanism applicable to Chinese educational culture has been proposed. The dual-path intervention strategy of “creating a supportive atmosphere and enhancing students’ sense of efficacy” is proposed for teacher training based on the empirical results, and specific suggestions are provided for the localization of CLT in Chinese classrooms, which is an important guiding value for improving the quality of English language teaching in China and promoting the innovation of teaching methods.